Effectiveness of Video Based Health Education in Improving Adolescent Girls’ Knowledge of Menstrual Hygiene Management - Rachmawaty M. Noer; Fitri; Siti Aisyah (Poltekkes Kemenkes Banten, 2026)
Adolescent girls are a vulnerable group to reproductive health problems, one of which is caused by low knowledge regarding menstrual hygiene management. Video media was chosen as a health education tool because it combines visual and audio elements that attract attention, match adolescent characteristics, and facilitate comprehension of the material. This study aimed to determine the effect of video-based health education on adolescent girls' knowledge of menstrual hygiene management at SMPN 63 Batam. This research employed a quantitative method with a pre-experimental design of the one-group pretest-posttest type. The sample consisted of 46 seventh-grade students who had experienced menstruation, selected through purposive sampling. The research instruments included a 14-item true-false menstrual hygiene management knowledge questionnaire and a 10-minute educational video. Data were collected through a pre-test before the intervention and a post-test after the intervention, and analyzed using the Wilcoxon nonparametric test. The results showed that before the intervention, most respondents were in the low knowledge category (54,3%), whereas after the intervention, the majority improved to the good category (91.3%). A p-value of 0.000 (p<0.05) indicated a significant difference in knowledge before and after the intervention. In conclusion, video-based health education was effective in improving adolescent girls knowledge of menstrual hygiene management. It is recommended that schools utilize video media as an interactive and appropriate health education method tailored to the needs of adolescents.